2004
DOI: 10.1016/j.jvs.2004.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous repair of abdominal aortic aneurysm

Abstract: Complete percutaneous treatment of AAA may have some advantages over open femoral artery access, but it is not free from risk. Percutaneous treatment of AAA can be completed successfully in most patients, but should be performed at an institution where conversion to an open procedure can be completed expeditiously if necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 19 publications
0
138
0
4
Order By: Relevance
“…There are reported series where failed p-EVAR has resulted in more blood loss then planned S-EVAR [19,20]. It is therefore of paramount importance that once a p-EVAR strategy has been chosen it is successful.…”
Section: Discussionmentioning
confidence: 99%
“…There are reported series where failed p-EVAR has resulted in more blood loss then planned S-EVAR [19,20]. It is therefore of paramount importance that once a p-EVAR strategy has been chosen it is successful.…”
Section: Discussionmentioning
confidence: 99%
“…However, percutaneous closure was more favorable with respect to mean operation duration, anesthesia time and the use of local or regional anesthesia (9,15,16). Patients often complained of back pain due to mandatory postprocedural bed rest, which was usually related to a coexistent pathological spinal condition that is frequently seen in this patient population (17).…”
Section: Discussionmentioning
confidence: 99%
“…7,36 Analyses examining hospital administrative data found that PEVAR led to decreased operative time. 28,47 One meta-analysis averaged the operative time in 8 studies and found that PEVAR was significantly shorter by ≈30 minutes (106 versus 145 minutes). 43 Another report examined the 2 different preclose methods and compared them with open femoral artery exposure and found that operative time was on average 34 minutes shorter in the ProGlide group and 46 minutes shorter in the Prostar group.…”
Section: Closure Devices For Endovascular Interventionsmentioning
confidence: 99%